2012
DOI: 10.1186/1756-9966-31-32
|View full text |Cite
|
Sign up to set email alerts
|

Human periprostatic adipose tissue promotes prostate cancer aggressiveness in vitro

Abstract: BackgroundObesity is associated with prostate cancer aggressiveness and mortality. The contribution of periprostatic adipose tissue, which is often infiltrated by malignant cells, to cancer progression is largely unknown. Thus, this study aimed to determine if periprostatic adipose tissue is linked with aggressive tumor biology in prostate cancer.MethodsSupernatants of whole adipose tissue (explants) or stromal vascular fraction (SVF) from paired fat samples of periprostatic (PP) and pre-peritoneal visceral (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
117
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 64 publications
10
117
0
3
Order By: Relevance
“…Our findings are in agreement with previously reported experimental systems testing various features in which adipocytes affect PCa growth: co-culture of PC-3 cells with rat epididymal adipocytes increased intracellular lipid content in cancer cells and stimulated their proliferation [52]. In vitro culture of PCa cells in the presence of adipocyte conditioned media (CM) was enough to promote increased proliferation and motility [53][54][55][56]. The critical factors present in the adipocyte CM were shown to be monocyte chemotactic protein-1 (MCP-1) [54], CC chemokine ligand 7 (CCL7) [56], and matrix metalloproteinases (MMPs) 2 and 9 [53,54].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are in agreement with previously reported experimental systems testing various features in which adipocytes affect PCa growth: co-culture of PC-3 cells with rat epididymal adipocytes increased intracellular lipid content in cancer cells and stimulated their proliferation [52]. In vitro culture of PCa cells in the presence of adipocyte conditioned media (CM) was enough to promote increased proliferation and motility [53][54][55][56]. The critical factors present in the adipocyte CM were shown to be monocyte chemotactic protein-1 (MCP-1) [54], CC chemokine ligand 7 (CCL7) [56], and matrix metalloproteinases (MMPs) 2 and 9 [53,54].…”
Section: Discussionsupporting
confidence: 82%
“…In vitro culture of PCa cells in the presence of adipocyte conditioned media (CM) was enough to promote increased proliferation and motility [53][54][55][56]. The critical factors present in the adipocyte CM were shown to be monocyte chemotactic protein-1 (MCP-1) [54], CC chemokine ligand 7 (CCL7) [56], and matrix metalloproteinases (MMPs) 2 and 9 [53,54]. Of note, conditioned media from PC-3 cells stimulated the expression of a range of adipokines and cytokines such as leptin, IL-6, and TNFα in adipose tissue explants [57].…”
Section: Discussionmentioning
confidence: 99%
“…These lipids can be derived from dietary lipoproteins in the circulation, which are hydrolyzed by lipoprotein lipase to free fatty acids, or be released by lipolysis from stores in local adipose tissue depots that comprises a major component of the tumor microenvironment (Ribeiro et al 2012). Androgens are generally viewed to stimulate lipolysis of fatty acids from adipocytes (O'Reilly et al 2014), and have been reported to induce the expression of cell surface proteins that regulate the uptake of lipids from the extracellular microenvironment, including phosphatidic acid phosphatase type 2 (Ulrix et al 1998) and plasma membrane fatty acid binding protein (Pinthus et al 2007).…”
Section: Androgens Stimulate Lipid Synthesis Uptake and Storagementioning
confidence: 99%
“…Ces études, bien que préliminaires, renforcent l'idée d'un rôle paracrine du TAPP dans la progression du cancer de la prostate, rôle qui pourrait être amplifié dans un contexte d'obé-sité. Les sécrétions du TAPP semblent avoir un effet sur le comportement des cellules prostatiques en stimulant leur prolifération ainsi que leurs capacités migratoires et invasives et cet effet est régulé par l'obésité [6]. De façon très intéressante, cette influence est moins prononcée pour les sécrétions du TAV que pour celles du TAPP suggérant, pour ce dernier, un profil de sécrétion spécifique.…”
unclassified
“…De façon très intéressante, cette influence est moins prononcée pour les sécrétions du TAV que pour celles du TAPP suggérant, pour ce dernier, un profil de sécrétion spécifique. Parmi les acteurs impliqués dans cet effet, on retrouve principalement l'IL6 et les métallopro-téases 1 2 et 9 [6]. Les sécrétions du TAPP pourraient donc influencer les propriétés invasives des cellules tumorales bien que ce concept n'ait pas été validé in vivo.…”
unclassified